Identificación de peligros y evaluación de riesgos en la actividad de crianza de vacunos en la facultad de agronomía. San Juan-Loreto-2019 - Cervan Garcia, Sol Arabia (2022)
The research work was carried out in the cattle project, located in the Faculty of Agronomy of the National University of the Peruvian Amazon in the District of San Juan Bautista, located 45 meters from the classrooms of the Faculty of Agronomy of the university city. This research began with the identification of the dangers in the handling processes in the cattle project, the registered dangers were evidenced for the valuation of the evaluated risks to the worker and the environment; likewise, the risks for each activity developed were evaluated. The evaluated risks allowed us to assess them by their level of significance and thus be able to establish control measures and minimize or mitigate the identified hazards and above all to perform a safe work. Most of the hazards and risks identified were exposure to microbiological agents (bacteria or other microorganisms) due to the lack of personal protective equipment (PPE) and sharps, among others of importance, in the daily work of the personnel involved in this activity. The identification of hazards and risk assessment and their respective evaluation in the cattle raising activity of the project allows the implementation of safety and health measures for the workers in this project, confirming the research hypothesis.